Melatonin Engineered Adipose-Derived Biomimetic Nanovesicles Regulate Mitochondrial Functions and Promote Myocardial Repair in Myocardial Infarction - Zhang, Yang; Yang, Ning; Huang, Xu; Zhu, Yan; Gao, Shan; Liu, Zhongyang; Cao, Feng; Wang, Yabin (Frontiers in Cardiovascular Medicine, 2022)
Myocardial infarction (MI), one type of ischemic heart disease, is a major cause of disability and mortality worldwide. Currently, extracellular vesicles (EVs) derived from adipose-derived stem cells (ADSC) have been proven to be a potentially promising therapeutic treatment for MI. However, the inconvenience of isolation, the low productivity, and the high cost of EVs greatly limits their application in clinic. In this study, we constructed novel biomimetic ADSC-derived nanovesicles (ADSC NVs) to achieve cell-free therapy for MI. Here, we firstly developed a novel Mel@NVs delivery system consisting of engineered ADSC NVs with melatonin (Mel). Then, the characterization and properties of Mel@NVs were performed. The effect of Mel@NVs on cellular oxidative stress and myocardial infarction repair was conducted. The results showed that Mel@NVs treatment under ischemia mimic condition reduced cell apoptosis from 42.59 ± 2.69% to 13.88 ± 1.77%. Moreover, this novel engineered Mel@NVs could ameliorate excessive ROS generation, promote microvessel formation, and attenuate cardiac fibrosis, which further alleviates mitochondrial dysfunction and finally enhance myocardial repair. Hence, the engineered NVs show a potential strategy for MI therapy.